Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Koperasi Komunitas Batik Bekasi (KOMBAS): The Influence of Organizational Culture and the Work Environment on Employee Performance at the Bekasi Batik Community Cooperative (KOMBAS) - Putri Eka Riana; Desy Suryani (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to analyze the influence of organizational culture and work environment on employee performance at the Batik Bekasi Community Cooperative (KOMBAS). Data analysis was conducted using a quantitative approach with multiple linear regression to test the effects of organizational culture and work environment on employee performance, processed using IBM SPSS for Windows version 25 software. The research data were obtained from questionnaires distributed to respondents. The sampling technique used was saturated sampling, with a total of 50 respondents. The results of the study showed that the F-count value of 18,731 > F-table 3.19, indicating that organizational culture and work environment have a positive and significant simultaneous effect on employee performance. Partially, the organizational culture variable had a t-count value of 2.902 > t-table 2,011, meaning that the alternative hypothesis (Ha) was accepted, and organizational culture has a positive and significant effect on employee performance. The work environment variable had a t-count value of 4.087 > t-table 2,011, meaning that the alternative hypothesis (Ha) was accepted, and the work environment has a positive and significant effect on employee performance. These findings have important implications for management in designing strategies to create a positive organizational culture and a supportive work environment in order to improve employee performance.